Plasma Exchange as A Rescue Therapy in Weil’s Disease with Severe Hyperbilirubinemia, Acute Renal Failure, And Multidrug-Resistant Organism Co-Infection: A Rare Case in Critical Care Setting - Debby Vania; Albert Frido Hutagalung (Journal of Biomedicine and Translational Research, 2023)
Background: Leptospirosis is a zoonotic infectious disease caused by spirochete Leptospira interrogans. Weil’s disease is a severe form of leptospirosis. In case of Weil's Disease which did not show improvement despite standard treatment with RRT and antibiotics, an additional therapeutic modality is needed as a rescue therapy in critical condition. Therapeutic plasma exchange (TPE) has been reported to showed positive outcomes in patient with sepsis and leptospirosis. However, TPE has not been widely used in treating severe leptospirosis. We report a case of Weil’s disease with severe hyperbilirubinemia, acute renal failure, and multidrug-resistant organism (MDRO) successfully treated with therapeutic plasma exchange (TPE) and intermittent renal replacement therapy (RRT).Case Presentation: A 25-year-old male developed Weil’s disease with severe hyperbilirubinemia and acute renal failure. The culture results showed that he was co-infected with multidrug-resistant organism. He failed to improve and fell into a septic shock while treated in the intensive care unit with empirical antibiotics and intermittent RRT. His serum bilirubin rises to 43.34mg/dL. Furthermore, he underwent single TPE and showed rapid clinical improvement with recovery of liver and renal function.Conclusion: Plasma exchange had a vital role in reducing serum bilirubin and removal of harmful substances. TPE as a rescue therapy can be used for further intensive care support in severe leptospirosis which has not shown improvement despite standard treatment with RRT and antibiotics.